2015
DOI: 10.1136/gutjnl-2014-309086
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer screening: a global overview of existing programmes

Abstract: Colorectal cancer (CRC) ranks third among the most commonly diagnosed cancers worldwide, with wide geographical variation in incidence and mortality across the world. Despite proof that screening can decrease CRC incidence and mortality, CRC screening is only offered to a small proportion of the target population worldwide. Throughout the world there are widespread differences in CRC screening implementation status and strategy. Differences can be attributed to geographical variation in CRC incidence, economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
991
1
32

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,039 publications
(1,033 citation statements)
references
References 106 publications
9
991
1
32
Order By: Relevance
“…Especially the comparison with colonoscopy screening, which is for example implemented in Austria, Greece and Poland, 43 is interesting because CTC and MRC have comparable test characteristics for large adenomas and CRC compared with colonoscopy screening [13][14][15][16][17][18][19][20][21] but are less invasive. Also, bowel preparation, which is an important barrier in colonoscopy screening, 7,44 is likely to be less burdensome for imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Especially the comparison with colonoscopy screening, which is for example implemented in Austria, Greece and Poland, 43 is interesting because CTC and MRC have comparable test characteristics for large adenomas and CRC compared with colonoscopy screening [13][14][15][16][17][18][19][20][21] but are less invasive. Also, bowel preparation, which is an important barrier in colonoscopy screening, 7,44 is likely to be less burdensome for imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, colorectal cancer screening participation differs, depending on the approach and test offered; 25 results of this study are limited to organised, FIT-based programmes; these are the most widely implemented in Europe, 26 but including only one test or approach could, nonetheless, be considered a limitation. Finally, because of socioeconomic differences identified between the participating centres (a recognised determinant of screening participation) the GP was the unit of randomisation; as a consequence, a negligible interprofessional contamination cannot definitively be ruled out as intervention and control professionals coexisted in the same centres.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Several trials have demonstrated that FIT screening is associated with a higher diagnostic yield and higher adherence compared with gFOBT screening. [5][6][7][8][9][10][11] As a consequence, several countries, including Italy, Australia, Japan, and the Netherlands, have adopted population-based FIT screening, 12 whereas in the United States, for example, several local initiatives recently adopted FIT screening. 12,13 New tests always raise the question of whether randomized controlled trials, which are expensive and take at least 10 years before results are produced, are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…5-11 As a consequence, several countries, including Italy, Australia, Japan, and the Netherlands, have adopted population-based FIT screening, 12 whereas in the United States, for example, several local initiatives recently adopted FIT screening. 12,13 New tests always raise the question of whether randomized controlled trials, which are expensive and take at least 10 years before results are produced, are necessary. To our knowledge, the long-term effectiveness of repeated FIT screening has not yet been studied empirically.…”
mentioning
confidence: 99%